Mitigating Simulator Adaptation Syndrome by means of tactile stimulation. (January 2017) - Gálvez-García, Germán; Albayay, Javier; Rehbein, Lucio; Tornay, Francisco
Abstract: Some drivers experience Simulator Adaptation Syndrome (SAS), a condition in which nausea, disorientation, dizziness, headache, and difficulty focusing, are exhibited when driving in a simulator. To reduce this syndrome, we investigated the efficacy of tactile stimulation (TS) on mitigating Simulator Adaptation Syndrome (SAS) in a driving simulation. Fifteen drivers (eight women; mean age = 24.07 years) participated in this experiment. We compared the total scores of the Simulator Sickness Questionnaire (SSQ) across two stimulation conditions (TS condition and no stimulation condition as a baseline measure). The experimental outcomes revealed that TS seemed to decrease SAS due to attentional distraction from the symptoms and not because of an improvement in balance ability. Highlights: Tactile stimulation to mitigate Simulator Adaptation Syndrome (SAS) was proposed. Tactile stimulation decreased SAS without an improvement in balance ability. Tactile stimulation decreased SAS due to attentional distraction from the symptoms.